A new anatomical facial reconstruction from CT slices based on Delaunay triangulation. (1st January 2011) - Menaka, R.; Eapen, Maya; Chellamuthu, C.
A method for three dimensional reconstruction cranio-facial structure from 2D CT slices is proposed in this work. The method involves preprocessing of the individual slices, contour finding, 3D coordinate generation, Delaunay triangulation and redundant tetrahedron removal. The results are compared with standard marching cube algorithm and with standard commercial 3D software. The performance is studied based on time complexity and improvement in resolution.